Tertiary students’ preferences on extracurricular activities for English learning: Voices from the field of Advanced Program in Biotechnology - Le, Xuan Mai; Ly, Thi Bich Thuy; Le, Thanh Thao (CTU Journal of Innovation and Sustainable Development, 2023)
In Vietnam, where English plays a vital role in the country’s development, extracurricular activities for English learning are considered an effective reform for enhancing citizens’ English proficiency. Previous studies have showed the positive impact of extracurricular activities on language learners’ outcomes. Yet, almost none of them has investigated students’ voices about what, how, when, and where they want these activities to be organized. This current study was employed to fill that gap in the field of biotechnology (advanced program). A 77-item questionnaire was sent to 148 students who learned biotechnology in an advanced program at a tertiary institution in the Mekong Delta of Vietnam. The results indicated the students preferred mental activities (M=4.00) to others. Moreover, they would like to travel to experience cultures from English-speaking countries (M=4.11). Further extracurricular activities were encouraged to be organized on their university campus (M=3.63). The students also preferred short-term activities at weekends to those that were organized over a long period. The study proposed a model for further extracurricular activities at the end of this writing.